Debating Hawala, Infrastructures and Critical Issues: A Continuum from Hawala to Blockchain Technologies? - MIRABILE, MARIO (CONfines de Relaciones Internacionales y Ciencia Política)
The paper aims to investigate the debate regarding the Informal Value Transfer Systems (IVTS), in particular that of hawala, a trust-based money transfer system. In this regard, analyzing the debate regarding hawala using primary and secondary sources, the paper demonstrates how hawala suffers forms of coercion --particularly after the September 11 attacks in the US--. But also, experts and academics dealing with human rights, the remittance market and financial inclusion advocate for a fair and sustainable development of the hawala system. The article offers a brief overview of the possibilities and main challenges offered by the application of blockchain-based technologies and the societal, institutional and technological issues arising from it. In particular, the paper reflects on the contemporary debate about the hawala system to explain -- why at the moment -- the category of continuum cannot be considered adequate to describe the relationship between hawala and blockchain technologies.